Executive Committee Minutes 2014-09-04 - Academic Senate:::::::::
Agenda – Approved. Minutes of 8/21/14 – Approved. Chair Report – R. Senghas. President Report. Provost Report. Vice Chair Report. Visit from Paul Draper re: Sustainability Executive Committee Vision, Mission and Goals. Next Senate presentation regarding GMC. EPC Report. SAC Report. Technical problems during this meeting, recording lost.